Violência obstétrica: uma violação aos direitos humanos das mulheres - Maciel, Giseli Silva (My University, 2023)
Obstetric violence is a phenomenon that occurs when healthcare professionals violate the rights and dignity of pregnant women during childbirth and prenatal care. This study investigated the prevalence, causes, and consequences of obstetric violence, as well as measures to prevent and combat it. The research involved a literature review, data analysis, and interviews with pregnant women and healthcare professionals. The main findings indicate that obstetric violence is a concerning reality in many regions of the world, affecting both the physical and mental health of women. Causes include inadequate training for healthcare professionals, the stigma surrounding pregnancy and childbirth, institutional pressures, and a lack of information among pregnant women about their rights. Consequences range from emotional trauma to physical health complications. To combat obstetric violence, measures such as the training of healthcare professionals, awareness of pregnant women's rights, and reforms in obstetric care policies are necessary. It is crucial to promote a care environment that respects the autonomy and dignity of pregnant women, ensuring that childbirth is a safe and positive experience for all women. [resumo fornecido pelo autor]
A violência obstétrica é um fenômeno que ocorre quando profissionais de saúde, durante o processo de parto e atendimento pré-natal, violam os direitos e a dignidade das gestantes. Este estudo investigou a prevalência, causas e consequências da violência obstétrica, bem como as medidas para preveni-la e combatê-la. A pesquisa envolveu uma revisão bibliográfica a respeito do tema. Os principais resultados indicam que a violência obstétrica é uma realidade preocupante em muitas regiões do mundo, afetando tanto a saúde física quanto a mental das mulheres. As causas incluem a falta de treinamento adequado para os profissionais de saúde, estigmatização da gravidez e parto, pressões institucionais e falta de informação das gestantes sobre seus direitos. As consequências vão desde traumas emocionais até complicações de saúde física. Para combater a violência obstétrica, medidas como a capacitação dos profissionais de saúde, conscientização das gestantes sobre seus direitos, e reformas nas políticas de atendimento obstétrico são necessárias. É fundamental promover um ambiente de cuidado que respeite a autonomia e dignidade das gestantes, garantindo que o parto seja uma experiência segura e positiva para todas as mulheres. [resumo fornecido pelo autor]
Keywords: Direitos das mulheres; Gestantes - Saúde